The high incidence of vascular thromboembolic events in patients with metastatic or unresectable urothelial cancer treated with platinum chemotherapy agents. Issue 5 (30th November 2015) - Tully, Christopher M.; Apolo, Andrea B.; Zabor, Emily C.; Regazzi, Ashley M.; Ostrovnaya, Irina; Furberg, Helena F.; Rosenberg, Jonathan E.; Bajorin, Dean F.
Abstract : BACKGROUND: The current study compared the incidence of vascular thromboembolic events (VTEs) in patients with metastatic or unresectable urothelial carcinoma (UC) who were treated with gemcitabine and carboplatin (GCb); gemcitabine, carboplatin, and bevacizumab (GCbBev); or gemcitabine and cisplatin (GCis). METHODS: Patients with UC who were treated with GCbBev on protocol were analyzed prospectively and 2 contemporary control cohorts receiving GCb or GCis were evaluated retrospectively. VTE was defined as either venous or arterial (myocardial infarctions or cerebral vascular accidents) thrombosis. VTEs were considered to be related to treatment if they occurred during treatment or within 4 weeks of the completion of treatment. Associations with chemotherapy regimen were tested using either the Fisher exact test or Kruskal‐Wallis test. Clinical factors associated with VTEs were analyzed using conditional logistic regression stratified by treatment regimen. RESULTS: Among 198 patients, VTEs occurred in 13 of 51 patients treated with GCbBev (26%), 22 of 92 patients treated with GCb (24%), and 8 of 55 patients treated with GCis (15%). Patient characteristics were significantly different between the treatment cohorts in terms of age, prior cystectomy, tumor location near pelvic vessels, Khorana risk group, and receipt of antiplatelet therapy. The incidence of VTE and type of VTE (arterial vs venous) did not differ by type of chemotherapy. Prior cystectomy was associated with an increased risk of VTE (odds ratio, 2.2; 95% confidence interval, 1.0‐4.9 [ P  = .047]). CONCLUSIONS: The incidence of VTE in Cis‐treated patients was similar to prior reports. However, the VTE rate in Cb‐treated patients was > 20%, a figure not previously defined in patients with UC and higher than expected. This high incidence of both Cis‐related and Cb‐related VTEs warrants greater awareness by treating physicians and deserves further study. Cancer 2016;122:712–721. © 2015 American Cancer Society . Abstract : Metastatic or unresectable urothelial cancer is associated with a high incidence of vascular thromboembolic events in patients treated with first‐line, combination, platinum‐based chemotherapy. The vascular thromboembolic event rate is high with both cisplatin‐based and carboplatin‐based therapy.